Kesiapan Program Studi Pendidikan Vokasional Teknik Elektro dalam Melaksanakan Praktik Industri - Irwanto Irwanto (Universitas Sarjanawiyata Tamansiswa, 2019)
Abstracts. This study aims to determine the readiness of 2017 Electrical Engineering Education (PTE) students in facing Industrial Practices (PI). The existence of Higher Education (PT) especially vocational education plays an important role in the nation's development going forward, because the current condition of globalization requires professional and skilled workers who must be able to work in accordance with their competencies. The development of increasingly sophisticated technology requires an increase in the quality of Human Resources (HR) who inevitably adapt to these changes. This research is a qualitative research using a descriptive approach. The population of this research is eight lecturers of PI supervisors and 32 PTE fifth semester students. The evaluation results show that PTE students are ready to do PIs, this is supported by the level of student knowledge, socialization carried out by PTE study programs as well as adequate basic skills of students. In the PTE student activities implementing PI has been going well which is supported by the ability of students to adapt in the industrial environment. PI assessment is done by paying attention to attendance, discipline, motivation, work quality, initiative, creativity, behavior and work skills.